حالة البحوث في السُّنَن الإلهية في بناء الأُمم والحضارات - al-Azm, Alia’ (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2023)
This study examines the scholarship conducted on the subject of al-Sunan al-Ilāhiyyah (Divine Law) in the context of nation and civilization building. It traces what thinkers in general have written about the laws that govern the construction of nations. It then uncovers how the subject of Divine Law in nation and civilization building is dealt with in Islamic thought, starting with the classical period and concluding with the situation in modern times. Following an inductive, descriptive, and critical methodology, the study finds that the subject was investigated by thinkers in the sixth century BCE, and that the so-called Renaissance in the Western world witnessed a vibrant intellectual activity that dealt with the same issue, producing terms and theories that impacted real life. On the other hand, the classical Islamic corpus showed no interest in writing about the issue due to its actual implementation in real life; writing about it began in the third century AH through allusions and studies that initiated theoretical awareness. As for modern times, one finds serious work within the scientific research accomplished in this field, which has prompted the endeavour to lay the foundations of a theoretical discipline, a philosophical approach and an operational mode of thought seeking to extricate the nation out of its civilizational crisis.